2012
DOI: 10.1111/tid.12014
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of low‐dose cidofovir in kidney transplant recipients with BK virus infection

Abstract: Background BK virus (BKV) infection in kidney transplant recipients is associated with progressive graft dysfunction and graft loss. Cidofovir, an antiviral agent with known nephrotoxicity, has been used in low doses to treat BKV infections. However, the systemic exposure and disposition of the low-dose cidofovir regimen is unknown in kidney transplant recipients. Methods We investigated the pharmacokinetics of low-dose cidofovir both without and with oral probenecid in 9 transplant patients with persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The limitation of this approach is that the pharmacokinetic criterion (area under the concentrationtime curve) is probably not the best predictor of cidofovir efficacy: Concentration in the kidney may be much higher than in plasma [20]. Moreover, the high affinity of cidofovir for the kidney may partially explain the virological response observed in some patients despite low systemic exposure [37]. Although the renal toxicity of cidofovir is now well documented, the impact of other drugs should be taken into account; almost all patients also received cyclosporine as part of transplantation care but also other nephrotoxic drugs (antibiotics, antivirals, antifungals).…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of this approach is that the pharmacokinetic criterion (area under the concentrationtime curve) is probably not the best predictor of cidofovir efficacy: Concentration in the kidney may be much higher than in plasma [20]. Moreover, the high affinity of cidofovir for the kidney may partially explain the virological response observed in some patients despite low systemic exposure [37]. Although the renal toxicity of cidofovir is now well documented, the impact of other drugs should be taken into account; almost all patients also received cyclosporine as part of transplantation care but also other nephrotoxic drugs (antibiotics, antivirals, antifungals).…”
Section: Discussionmentioning
confidence: 99%
“…The use of adjuvant low-dose CDV therapy was shown to result in prolonged graft survival and stabilized graft function in renal transplant recipients suffering from BKPyV interstitial nephritis (Kuypers et al, 2005). A recent study has demonstrated that CDV clearance and the mean estimated glomerular filtration rate in renal transplant recipients with persistent BKPyV viremia without nephropathy were linearly related irrespective of probenecid administration (Momper et al, 2013). Based on this relationship, the systemic exposure to CDV in individual patients can be predicted and may be used to evaluate exposure-response relationships to optimize CDV dosing regimen for BKPyV infection.…”
Section: In Vitro In Vivo and Clinical Evidences For The Anti-polyommentioning
confidence: 99%
“…Although cidofovir has long been known to inhibit the replication of polyomaviruses in culture, its mechanism of action has remained uncertain (38,39,57). Here, we show that cidofovir can inhibit MCPyV replication.…”
Section: Discussionmentioning
confidence: 60%
“…Cidofovir is a potent inhibitor of polyomavirus replication (38,39,57). Although its active metabolite, cidofovir diphosphate, is known to inhibit viral DNA replication by selectively inhibiting virally encoded DNA polymerases, polyomaviruses do not encode any polymerases.…”
Section: Mutation Of the Fe/s Cluster-coordinating Cysteines Inmentioning
confidence: 99%